Respuesta :
From the given functions, the value of (g-f)(2)=1
Given :
The functions are
[tex]f(x)=\frac{x+3}{x^2-x-12} \\g(x)=log_4(x)[/tex]
Lets evaluate (g-f)(2)
[tex](g-f)(2)=g(2)-f(2)[/tex]
To find out g(2), replace 2 for x in g(x) and then replace 2 for x in f(x)
[tex]f(x)=\frac{x+3}{x^2-x-12} \\g(x)=log_4(x)\\x=2\\f(2)=\frac{2+3}{2^2-2-12}=\frac{5}{-10}=-\frac{1}{2} \\\\g(2)=log_4(2)=\frac{1}{2}[/tex]
Now we find g(2)-f(2)
[tex](g-f)(2)=g(2)-f(2)=\frac{1}{2}-\frac{-1}{2} =1[/tex]
Learn more : brainly.com/question/15038769